Missionary positions : a postcolonial feminist perspective on sex work and faith-based outreach in Australia - McGrow, Lauren. (Theology in Practice, 2017)
Missionary Positions examines the context for Christian outreach to people in the sex industry. Over the last 20 years, faith-based organisations have become more engaged in ministering with sex workers. But what are the methods and desired outcomes that undergird pastoral practice in this field? Most Christians see prostitution as evil, and those who sell sex are considered broken victims in need of restoration. Yet the voices and experiences of sex workers themselves often challenge these assumptions. Using feminist and postcolonial perspectives, interviews with Christian practitioners in Australia and personal narrative, Lauren McGrow carves out a space for the dynamic theological agency and life complexity of sex workers to be more fully acknowledged in faith-based outreach projects.